Nitrous oxide supersaturation at the liquid/air interface of animal waste - Makris, Konstantinos C.; Andra, Syam S.; Hardy, Michael; Sarkar, Dibyendu; Datta, Rupali K.; Bach, Stephan B H; Mullens, Conor P. (My University, 2009)
Concentrated animal feeding operations around the globe generate large amounts of nitrous oxide (N2O) in the surrounding atmosphere. Liquid animal waste systems have received little attention with respect to N2O emissions. We hypothesized that the solution chemistry of animal waste aqueous suspensions would promote conditions that lead to N2O supersaturation at the liquid/air interface. The concentration of dissolved N2O in poultry litter (PL) aqueous suspensions at 25 °C was 0.36 μg N2O mL−1, at least an order of magnitude greater than that measured in water in equilibrium with ambient air, suggesting N2O supersaturation. There was a nonlinear increase in the N2O Henry constants of PL from 2810 atm/mole fraction at 35 °C to 17 300 atm/mole fraction at 41 °C. The extremely high N2O Henry constants were partially ascribed to N2O complexation with aromatic moieties. Complexed N2O structures were unstable at temperatures > 35 °C, supplying the headspace with additional free N2O concentrations.
Keywords: Animal waste; Henry constant; Lagoons; Liquid/air interface; Nitrous oxide; Supersaturation